feasibility of considering professional sports competitions as literary and artistic works - Mahmoud Hekmatnia; Rahim Pilvar; Masoud Zangene (پژوهشنامه حقوق تطبیقی, 2021)
Sport, like other industries, has products and goods that may be based on skill, art, thought and knowledge. With a glance, it's possible to see professional sports competitions and surrounding affairs as the source of products that are shaping up in the industry. One of the achievements of these races is the sale of points, television broadcasting, ticket sales, promotions, and the like; among them the most profitable is the sale of sporting media player points, which are in the form of a contract, club or league or sports federation, the right to broadcast The contest settles in a variety of ways to an organization or company that specializes in broadcast media. Regardless of the level of commercial importance and popularity of professional sports competitions, one of the most important doubts is whether a set of professional sports competitions can be protected as literary and artistic work as intellectual property rights? This research seeks to prove, with the help of the fundamental principles of literary and artistic works, that professional sports competitions have the ability to take into account the truthfulness of the aspects of originality and expression in a particular form and form of the case of literary and artistic works of thought And hence the monitory and moral rights arising from literary and artistic works.